Hubungan Higiene Sanitasi Dengan Kontaminasi Escherichia coli dan Jumlah Total Kuman Pada Cincau Hitam di Pasar Tradisional Kota Semarang - Rosyida, Arina; Martini, Martini (Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2023)
Black grass jelly sellers at traditional market generally have less attention to hygiene and sanitation. That condition can cause the black grass jelly to be contaminated by bacteria, especially Escherichia coli that can cause diarrhea. The purpose of this study is to analyze higiene sanitation factors that are associated with total plate count and E.coli contamination on black grass jelly. The sample of this study are thirty black grass jelly sellers at 16 traditional market in Semarang that selected by using non-probability sampling with saturation sampling technique. Data analyses include descriptive and analytical by using fisher exact test. Descriptive analysis shows the percentage of total plate count in all black grass jelly are not eligible (100%), all samples are contaminated by E.coli (100%), black grass jelly sanitiation is not eligible (93,3%), seller hygiene is not eligible (93,3%), equipment sanitation is not eligible (93,3%), and enviromental sanitation is not eligible (96,7%). The result of statistical test by using fisher exact shows factor that is correlated with E.coli contamination is black grass jelly sanitation (p =0.002), whereas uncorrelated factors are seller hygiene (p=0.99), equipment sanitation (p=0.99), and environmental sanitation (p=0.99). The advice is that black grass jelly seller should pay more attention to hygiene and sanitation. People should be more careful when they buy black grass jelly. In addition, local health agencies should provide guidance to black grass jelly seller seller about hygiene and sanitation, and do the monitoring more strictly.